Dentists' restorative decision‐making and implications for an 'amalgamless' profession. Part 3: Dentists' attitudes. (December 2016) - Alexander, G; Hopcraft, MS; Tyas, MJ; Wong, RHK
Abstract: Background: The Minamata Convention has agreed to a worldwide reduction in the production and use of mercury‐containing products and processes. This will change the approach to use of direct restorative materials in the future. There is little research exploring the attitudes of dentists to any change. Methods: A survey relating to the use of direct restorative materials was distributed to dentists who were members of the Australian Dental Association or Members and Fellows of the Royal Australasian College of Dental Surgeons. Data were statistically analysed. Results: There were 408 respondents. Responses to statements concerning attitudes toward a phase‐down of amalgam depended on whether the respondent used amalgam, year of primary dental qualification and association with academia. Thirty per cent of respondents indicated they do not use amalgam. The mean use of amalgam for all direct restorative procedures was 18%. Conclusions: Dentists are concerned over potential implications of a phase‐down of amalgam and much should be done to address these concerns. Many dentists are undecided as to what are the implications, which may reflect a lack of understanding of the issues. It is incumbent on policy‐makers to produce and disseminate information relating to the issues identified by this research.